ORNE Learning Model to Improve Problem-Solving Skills of Physics Bachelor Candidates: An Alternative Learning in the Covid-19 Pandemic - Binar Kurnia Prahani; Ali Hasbi Ramadani; Diah Hari Kusumawati; Nadi Suprapto; Madlazim Madlazim; Budi Jatmiko; Zainul Arifin Imam Supardi; Husni Mubarok; Shabrina Safitri; Utama Alan Deta (Jurnal Penelitian Fisika dan Aplikasinya (JPFA), 2020)
In this industrial revolution 4.0 era, professional science, technology, engineering, and mathematics (STEM) bachelor must have various skills. One of which is problem-solving skills. The development of problem-solving skills (PSS) is very important in higher education. Students must have PSS that must be improved to become excellent graduates, including physics bachelor candidates. Many physics bachelor candidates lack problem-solving skills. This problem is the basis for developing innovative learning models based online that, by design, can improve the problem-solving skills of physics bachelor candidates in the COVID-19 pandemic. This research aims to analyze the effectiveness ORNE learning model in improving the problem-solving skills of physics bachelor candidates as an alternative to online learning in the COVID-19 pandemic. The research design used a true-experiment with a non-equivalent control group design with 58 physics bachelor candidates. Data collected using the problem-solving skills test and then analyzed using the Paired Sample Test, Effect Size, N-gain, and Independent Sample Test. The results showed that the ORNE learning model proved effective in improving physics bachelor candidates' problem-solving skills. This research implies that the ORNE learning model can improve physics bachelor candidates' problem-solving skills as an alternative to online learning in the COVID-19 pandemic.